2018
DOI: 10.3389/fpls.2018.01455
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Chinese Cabbage Reveals Correlation Between Rosette Leaf and Leafy Head Variation

Abstract: To understand the genetic regulation of the domestication trait leafy-head formation of Chinese cabbages, we exploit the diversity within Brassica rapa. To improve our understanding of the relationship between variation in rosette-leaves and leafy heads, we phenotyped a diversity set of 152 Chinese cabbages. This showed correlation between rosette-leaf traits and both head traits and heading capacity. Interestingly, the leaf number of the mature head is not correlated to heading degree nor head shape. We then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
3
17
1
Order By: Relevance
“…At the QTL level, we detected QTLs for rosette leaf-, outer heading leaf-, and leafy head-related traits in this study. We did not detect the same QTLs for rosette LL and width or rosette LPL compared to the previous QTL study 9 . In addition to environmental variation, in these studies, the timing of phenotypic data collection differed: we measured the rosette leaf traits at the heading stage in this study, but phenotyped the growing rosette leaves at rosette stages (30, 34, 37, 41, 44, and 48 days after sowing (DAS)) in a previous QTL study.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…At the QTL level, we detected QTLs for rosette leaf-, outer heading leaf-, and leafy head-related traits in this study. We did not detect the same QTLs for rosette LL and width or rosette LPL compared to the previous QTL study 9 . In addition to environmental variation, in these studies, the timing of phenotypic data collection differed: we measured the rosette leaf traits at the heading stage in this study, but phenotyped the growing rosette leaves at rosette stages (30, 34, 37, 41, 44, and 48 days after sowing (DAS)) in a previous QTL study.…”
Section: Discussioncontrasting
confidence: 90%
“…However, in Chinese cabbage, rosette leaves remain active until the leafy heads mature, likely performing photosynthesis in the fast-growing leafy head 18 . Both this study and previous studies showed a correlation between the size and shape of rosette leaves and leafy head shape 6 , 9 . HTS is clearly associated with outer rosette LL and leaf petiole length (LPL) (this study).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations